2012
DOI: 10.1002/aoc.1870
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of amides from imines using Et3SiH/Zn system

Abstract: A simple and efficient approach for the synthesis of amides by the reaction of imines and acyl chlorides in the presence of Et3SiH/Zn system in THF at ambient temperature is reported. Mild reaction conditions, good yields of products, short reaction time and operational simplicity are the advantages of this procedure. Copyright © 2012 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Ghaffarzadeh et al suggested a method for fentanyl synthesis by the reduction of Schiff base 2.22.d in the presence of propionic anhydride (Scheme ). , The reaction yielded 280 mg of the product (84%) with an RME of 26%.…”
Section: Drugs Affecting the Central Nervous Systemmentioning
confidence: 99%
“…Ghaffarzadeh et al suggested a method for fentanyl synthesis by the reduction of Schiff base 2.22.d in the presence of propionic anhydride (Scheme ). , The reaction yielded 280 mg of the product (84%) with an RME of 26%.…”
Section: Drugs Affecting the Central Nervous Systemmentioning
confidence: 99%
“…The amide linkages appear as an important structural component in peptides, many natural polymeric products, and pharmaceuticals. They are not only the primary chemical links between proteins and pharmaceuticals, but they are also the foundation for some of the most commonly used synthetic polymers [1,4,8] . Heating a mixture of amine and an acid, Jursic, and Zdravkovski [9] have elucidated as the method of choice for the direct synthesis of many amides.…”
Section: Introductionmentioning
confidence: 99%